Dry beans and pulses: Production, processsing and nutrition - Siddiq, Muhammad; Uebersax, Mark A. (Hoboken Wiley, 2022)
New chapters address Hard-to-cook phenomenon and other storage-induced quality defects, quality assessment of raw and processed legumes using innovative technologies, utilization of dry beans and pulses as ingredients in diverse food products, and the production, processing, and nutritional profile of Faba beans and chickpeas and lentils
Keywords: Công nghệ Thực phẩm